L’aggravation du risque en assurance de responsabilité professionnelle ou mieux vaut prévenir que guérir - Borgia, Denis (Assurances)

(untitled) (HEC Montréal, 1989)
Mr. Denis Borgia, one of our collaborators, looks at aggravation in risks from a totally new angle: the problems involved, the consequences and the possible solutions as regards the aggravation in professional liability risks. Such a reflection is very interesting both for the insurer and the insured and the solutions offered, though avant-garde, may be taken from real life and from the practice of insurance.